FORMULASI DAN EVALUASI FISIK SEDIAAN TABLET NANOPARTIKEL EKSTRAK DAUN DADANGKAK (Hydrolea spinosa L.) - Niah, Rakhmadhan; Wahyuono, Subagus; Prihandiwati, Erna (Jurnal Insan Farmasi Indonesia, 2024)
The utilization of traditional medicines offers a safer alternative for treatment, particularly regarding side effects and toxicity. One herbal plant known for its antioxidant activity is dadangkak leaves (Hydrolea spinosa L.), containing flavonoids, polyphenols, and tannins. Ethanolic extracts of dadangkak leaves with antioxidant potential need development into tablet dosage forms. This study aims to determine the optimal formula for nanoparticle tablets containing dadangkak leaf extract. The extract was obtained via maceration using 96% technical ethanol, followed by evaporation to produce a thick extract. Nanoparticles were prepared by mixing the extract with 96% technical ethanol, distilled water, a chitosan solution in acetic acid, and a NaTTP solution. Particle size was analyzed using a Particle Size Analyzer (PSA). Tablet formulations involved varying concentrations of Na alginate and Avicel PH 102, using direct compression. Results showed that Na alginate and Avicel PH 102 concentrations affected tablet physical properties. Avicel PH 102 increased hardness and disintegration time, while Na alginate increased friability. Based on evaluations, formula 2 was determined to be the best.